Fourth Grade Elementary School Mathematics Learning Online Test - Sakin Sabila; I Made Suarjana; Made Sumantri (Jurnal Ilmiah Sekolah Dasar, 2021)
Teachers have difficulty checking student work. This is because all learning processes are carried out using HP media. In addition, in the learning process during the Covid-19 period, the teacher evaluates or provides other tasks only via Whatsapp. This study aims to create an online test for fourth-grade elementary school mathematics learning. The type of research used in this research is research and development. The model used in this study is using the ADDIE model. The research subjects were 2 experts in learning mathematics, and the experiment was conducted on 28 students in elementary school. The method used to collect data in this study used interviews and online tests. The data analysis techniques used are validity, reliability, discriminating power, difficulty level, quality of distractors, practitioner responses, and student responses. Instruments that have been designed to collect data are then tested first in order to find out the validity of the instrument. The result of the research is the analysis of the content validity test, and the items are at very high criteria. The results of the reliability test, the instrumenttested has a very high consistency. In the analysis of practitioner responses and student responses, the category is outstanding. So, the online test instrument for learning mathematics for fourth-grade elementary school students is valid and feasible to be used as an instrument for assessing student learning outcomes. This research implies that teachers can use the developed online test instrument to measure students' understanding during the learning process.